Irritable Mood as a Symptom of Depression in Youth: Prevalence, Developmental, and Clinical Correlates in the Great Smoky Mountains Study - Stringaris, Argyris (Elsevier, 2013)
OBJECTIVE: DSM-IV grants episodic irritability an equal status to low mood as a cardinal criterion for the diagnosis of depression in youth, yet not in adults; however, evidence for irritability as a major criterion of depression in youth is lacking. This article examines the prevalence, developmental characteristics, associations with psychopathology, and longitudinal stability of irritable mood in childhood and adolescent depression. METHOD: Data from the prospective population-based Great Smoky Mountains Study (N = 1,420) were used. We divided observations on 9- to 16-year-olds who met criteria for a diagnosis of depression into 3 groups: those with depressed mood and no irritability, those with irritability and no depressed mood, and those with both depressed and irritable mood. We compared these groups using robust regression models on adolescent characteristics and early adult (ages 19–21 years) depression outcomes. RESULTS: Depressed mood was the most common cardinal mood in youth meeting criteria for depression (58.7%), followed by the co-occurrence of depressed and irritable mood (35.6%); irritable mood alone was rare (5.7%). Youth with depressed and irritable mood were similar in age and developmental stage to those with depression, but had significantly higher rates of disruptive disorders. The co-occurrence of depressed and irritable mood was associated with higher risk for comorbid conduct disorder in girls (gender-by-group interaction, F(1,132) = 4.66, p = .03). CONCLUSIONS: Our study findings do not support the use of irritability as a cardinal mood criterion for depression. However, the occurrence of irritability in youth depression is associated with increased risk of disruptive behaviors, especially in girls.